Development of an IoT-based Heart and Lung Monitoring Device at Baubau Regional Hospital - Maibara, Rais; Sahibu, Supriadi; Jalil, Abdul (Sistemasi: Jurnal Sistem Informasi, 2025)
Cardiovascular diseases and lung infections require intensive monitoring, especially for high-risk patients. The limited number of specialist doctors at Baubau Regional Hospital often leads to delays in patient treatment. This study aims to develop an Internet of Things (IoT)-based health monitoring system that detects heart rate, oxygen saturation, and body temperature in real time using MAX30100 and DS18B20 sensors. The collected data is transmitted to Firebase and displayed on an Android application to facilitate remote monitoring. Testing results show an accuracy rate of 98.46% for heart rate, 98.6% for oxygen saturation, and 99.04% for body temperature, with deviations remaining within medically acceptable limits. The system’s preliminary diagnoses closely matched those of medical professionals, indicating its potential as an effective tool for early health risk detection and for supporting clinical decision-making.